Advancements and Challenges of Cobalt–Zeolite Composite Catalysts in Heterogeneous Catalysis - Wanying Liang; Guangyue Xu (Chemistry, 2025)
Cobalt–zeolite composite catalysts (Co–zeolite) and their heterogeneous catalytic systems have garnered significant research attention owing to their superior catalytic activity and cost-effectiveness. The speciation of cobalt within these catalysts—either through impregnation onto the zeolite framework or structural incorporation within the aluminosilicate matrix—is critically governed by the employed synthesis methodology, which subsequently dictates their distinct catalytic advantages in targeted reaction systems. Compared to homogeneous catalytic systems, heterogeneous Co–zeolite configurations demonstrate enhanced structural integrity that effectively mitigates cobalt leaching, thereby improving catalyst recyclability while minimizing environmental contamination. This review systematically examines recent advancements in Co–zeolite fabrication techniques and their catalytic performance across diverse applications, including Fischer–Tropsch synthesis, nitrogen oxide abatement, hydrogenation processes, and oxidative transformations. Particular emphasis is placed on elucidating the metal-framework interactions, with analysis of synergistic effects arising from multi-valent cobalt speciation and bimetallic cooperativity between cobalt and secondary transition metals. This work critically evaluates current challenges in Co–zeolite catalyst design. Finally, we propose future research directions focusing on a precise identification of active species and mechanistic elucidation, innovative synthesis strategies for cobalt speciation control, machine learning-guided catalyst optimization, and the advancement of eco-friendly catalysts.